Pizza dreams do come true - Higgins, Cam (Higgins, Cam. Ratnip, 2025)
When Ratnip and his sister Anchovy cannot find any pizza in the trashcans of the city, they gather their other siblings, Pepperoni, Marg, and Veggie, to make a whole pizza of their own.